On groups with a strongly imbedded subgroup having an almost layer-finite periodic part - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study Shunkov groups with the following condition: the normalizer of any finite nonunit subgroup has an almost layer-finite periodic part. It is proved that such a group has an almost layer-finite periodic part if it has a strongly imbedded subgroup with almost layer-finite periodic part.